Health education strategies for older people: experiences and challenges - Rodrigo Euripedes da Silveira; Francielle Toniolo Nicodemos Furtado de Mendonça; Álvaro da Silva Santos; Elvira Maria Ventura Filipe (Universidad de Alicante, 2015)
This is an integrative review which aims to assess the scientific literature related to health education for elderly in Brazil, between 2007 to 2013. How to search databases used the Virtual Health Library - VHL, Scielo, Redalyc and from the intersection of descriptors: aged and health education. Rose 14 articles that responded to the goals and, that after reading it he elucidated three categories, namely: Experiences in health education with elderly people, Experiences of training and capacity-building needs related to health education and physical activity as a tool for health education for the elderly. It turns out that one of the main gaps are the extension of studies and experiences with didactic approaches further, the appreciation of aspects beyond diseases, as well as the importance of physical activity, but also issues such as leisure, income generation, family relationships, in addition to better training of health professionals to deal with health education activities for the elderly.